Hubungan Pola Komunikasi Penyuluh Pertanian Lapangan (PPL) dengan Penerapan Teknik Budidaya Sayuran Sawi di Kecamatan Paal Merah Kota Jambi - Widyaningrum, Anty; Jamaludin, Jamaludin; Kurniasih, Siti (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
Agricultural extension activities are one of the efforts to change farmers' behaviour and develop farmers, including knowledge, skills and attitudes. This is done to realize agricultural development where one of the goals is to increase productivity. The objectives of this study are 1) knowing the communication patterns carried out by field agricultural extension workers, 2) knowing the level of application of mustard cultivation technology, and 3) knowing the relationship between communication patterns and the application of mustard cultivation techniques. This research was carried out in Paal Merah Sub-district and the Lingkar Selatan Village of Jambi City. The selection of the site was made deliberately. The sample in this study was 53 mustard farmers in both villages. This study used descriptive analysis and correlation analysis with the Spearman Rank method. The results showed that the communication patterns carried out were one-way communication patterns, two-way communication patterns, and multi-directional communication patterns. As a result, 92.45% of mustard farmers are at the level of application of high category mustard cultivation techniques, and 7.55% are in a low category. Based on the results of spearman rank analysis, it is known that the pattern of one-way communication is not related to the level of application of mustard cultivation techniques; the relationship category is weak and has a negative direction. On the other hand, the two-way and multi-directional communication patterns are related to the degree of application of mustard cultivation techniques, including the category of strong relationships and having a positive direction.